A Comparative Assessment of Postoperative Analgesic Efficacy of Lornoxicam versus Tramadol after Open Reduction and Internal Fixation of Mandibular Fractures. Issue 3 (September 2017) - Jain, Ankesh Dilip; Ravisankar, VSM; Siva Bharani, KSN; Sudheesh, KM; Tewathia, Nisha
Pain after any surgical procedure is inevitable but can be controlled by administration of analgesics in most cases. Postoperative pain after surgical treatment of mandibular fractures can be treated by nonsteroidal anti-inflammatory drugs (NSAIDs) and opioid analgesics. The purpose of this study is to critically compare the postoperative analgesic efficacy of small doses of intravenous TRAMADOL (opioid analgesic) versus LORNOXICAM (NSAID) in patients with mandibular trauma undergoing open reduction and internal fixation (ORIF) and to assess the presence of any adverse effects due to NSAID or opioid use. Forty adult ASA grade I–II patients with mandibular trauma, scheduled for ORIF under general anesthesia in the Department of Oral and Maxillofacial Surgery, College of Dental Sciences, Davangere, were selected for the study. The patients were randomly assigned into a tramadol group (Group T) and a lornoxicam group (Group L) and were administered intravenous tramadol 50 mg and intravenous lornoxicam 8 mg, respectively, at specific postoperative intervals. Pain intensity was quantitatively assessed at the 2nd, 4th, 6th, 12th, and 24th postoperative hours using a visual analog scale of 10 cm. Adverse effects of the analgesics were also recorded and compared. Both the drugs resulted in a significant decrease in pain intensity from 2nd to 24th postoperative hours, but better pain control was observed in Group L at 24th postoperative hour. Only two patients experienced nausea and vomiting in Group T and one patient experienced gastric acidity in Group L. The comparative results clearly demonstrate that pain control by intravenous lornoxicam is significantly better than by intravenous tramadol at 24th postoperative hour after ORIF of mandibular trauma. Side effects produced by both the drugs were minor and had no apparent effect on the study results.